Buy or Bye? Youth Recycling Fashion from Theory of Planned Behavior Perspective - Ifthiharfi, Ratu; Dewanti, Yunita; Halida, Rizka (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2025)
Recycling is a potential solution to address the issue of fabric waste driven by fast fashion. This study aims to examine the influence of behavioral, normative, and control beliefs on attitude, subjective norm, and perceived behavioral control to predict fashion recycling intention based on Theory of Planned Behavior (TPB). Data were collected from 316 Generation Y and Z participants using a convenience sampling approach. The questionnaire was developed through an elicitation study based on TPB constructs. Structural Equation Modeling was conducted and produced an acceptable model fit: χ² (369) = 693.28, p < .001; RMSEA = .060. This study found that behavioral, normative, and control beliefs significantly predicted their respective TPB variables. Crucially, subjective norm and perceived behavioral control directly predicted intention, with notable indirect effects from normative and control beliefs. This showed that interventions should focus on strengthening social influence and facilitating recycling behavior through increased perceived control.